Comparing radiological union between single spiral blade proximal femoral nail and double integrated locking screws proximal femoral nail in treating trochanteric femur fractures with rush scoring system - Krishnan, Kharthik (2019)
ABSTRACT Introduction: Proximal femoral nails are one of the most commonly and preferred used cephalomedullary implant used to treat trochanteric region femur fractures. These nails have shown to be more biomechanically stable in unstable trochanteric fractures compare to the extramedullary devices. However the assessment of radiological union on radiographs post operatively is not commonly measured. RUSH scoring on the other hand is a previously validated scoring system for assessing radiological union in proximal hip fractures. Aim: To compare the radiological union using RUSH score between the single spiral blade proximal femoral nail (PFNA) and the double integrated locking screws proximal femoral nail (INTERTAN) in treating trochanteric femur fractures in Hospital Tengku Ampuan Rahimah Klang and assess intraoperative complications arising in both the groups. Methodology: A retrospective study comparing 2 group of patients with trochanteric femur fractures who underwent 2 types of proximal femoral nails. Total of 74 patients with 37 patients in each arm were included in this study. Their post-operative x-rays at 6 weeks, 12 weeks and 24 weeks were taken together with their folders and reviewed for RUSH scoring by 2 different accessors. The sociodemographic data and the intraoperative complications were noted and recorded. The RUSH scores for both the groups were tabulated and then analysed to see any statistical significant difference in union rates in terms of RUSH scores.